Old-Timers, Newcomers, and Cultural Heritage: Interactions and Conflicts in Lithuanian Local Communities - Strazdaitė, Rugilė (Lietuvos istorijos studijos, 2025)
Cultural heritage may become relevant and beneficial for summoning local communities and forming their shared identity. Yet, in reality, there are the two sides of these interactions, and not merely the positive one. The main issue investigated in this article pertains to the developments experienced by local communities when, along with the old-time residents, newcomers are becoming more and more numerous, who are also referred to as invaders. These newcomers are new residents coming from elsewhere. These are also new businesses created by non-locals, new institutions, and their staff – those who are not the locals. Upon moving in and settling down, the newcomers start using the local heritage as well. The changes taking place in the structure of the local population, along with cultural tourism, whim has been getting ever more popular, as well as other realia invite to take a closer look at the impact being made on the local communities, primarily on the ‘old-timers’ of the place: Could these developments prompt the old-timers to take note of the cultural heritage surrounding them, and develop a novel perception of this heritage, or maybe this brings more conflicts than collective developments?When exploring the interactions between the ‘old-timers’ and the newcomers regarding the heritage, as well as the developing trends, a pattern is observed that newcomers, wherever they constitute larger or more active groups, tend to gather into separate communities or create social bubbles of their own. Although newcomers do consider the presence of the local ‘old-timers’, more commonly, they seek to fulfill their own objectives, whereas the ‘old-timers’ treat the newcomers somewhat more pragmatically. Heritage is also perceived in different ways: while the newcomers are more interested in the tangible heritage, the ‘old-timers’ find intangible heritage to be of more relevance as it is more appropriate for building up their sense of community. The study cases reveal that heritage becomes a source of not only communication, but also conflicts, as the ‘old-timer’ communities develop a feeling of getting deprived of the local heritage.
Keywords: local communities; cultural heritage; sense of community; conflicts; small towns